Study of Thermal Degradation of Zinc and Boron based Lubricant Additives using Fourier Transform Infrared and Nuclear Magnetic Resonance Spectroscopy - Faisal, Abrar (2011)
Zinc Dialkyl Dithiophosphates were used as anti-wear and anti-oxidants in lubricants from late 1950s. They are undoubtedly the most used anti-wear additive in the world right now. However it can cause environmental hazards by polluting the catalyst. It can also cause eye irritation and allergic contact dermatitis. Due to these reasons lubrication industry needs an alternative for the ZDDPs to replace it practical applications. Boron based compounds are already been studied as anti-wear additives for years now. They also make very good tribofilm on the surface of the metals to give protection form wear and tear. A lot of study was already done on these additives and their behavior in different atmospheres, but still there is a need for further study and research in the field. In this context this research study was carried out in the Department of Chemical Engineering, Luleå University of Technology. Iso-Butyl Zinc Dialkyl Dithiophosphate (ZDDP) and S-(di-n-dialkylborate)-ethyl-O,O’-dialkyldithiophosphates (BEDTP) were the two types of anti-wear agents used in this study. Solutions of these additives were made in different base oils and they were heated for different intervals of time. The samples before and after heating were characterized using Fourier Transform Infrared Spectroscopy (FTIR) and Nuclear Magnetic Resonance (NMR) techniques. The results of this study were discussed and concluded in this report. Validerat; 20110128 (anonymous)